An Appraisal of Growth and Instability of Marine Fish Production in Karnataka, India - Viswanatha, B. S.; Senthiladeban, R.; Infantina, J. A.; Rajakumar, M.; Leo Cyril, A. R. (Fishery Technology, 2016)
This study attempts to understand the growth and instability of marine fish production using secondary fisheries related data of Karnataka for the period 1980-2010. Craft-wise decadal growth rate of marine fish production was measured using Compound Growth Rate (CGR) and instability was studied by using Coppock Instability Index (CII) and Coefficient of Variation (CV). The results showed high instability in the number of purse seiners and gillnetters and longliners during 1980-90 (D1) and trawlers and rampanies during 1990-00 (D2). The growth rate of purse seine boats and other mechanised boats was more during 1980-90 (D1) and for trawler and rampanies during 1990-00 (D2). The maximum instability and growth rate for the purse seiners’ harvest was seen during 1990-00 (D2) and 1980-90 (D1) respectively. Similarly for trawlers, peak harvests occurred during 2000-10 (D3) and for other mechanized boats and rampanies it occurred during 1980-90 (D1). The instability in terms of CPUE for purse seiners was the highest during 1990- 00 (D2), whereas the overall growth rate in terms of CPUE showed negative trend. Likewise, peak instability and growth rate in terms of CPUE for trawlers and other mechanised boats was observed during 2000-10 (D3) and 1980-90 (D1) respectively. The overall growth rate in terms of CPUE for rampanies was negative, since their overall number increased during the entire study period.